Molecular characterization of tsetse's proboscis and its response to Trypanosoma congolense infection. - Erick O Awuoche; Brian L Weiss; Aurélien Vigneron; Paul O Mireji; Emre Aksoy; Benson Nyambega; Geoffrey M Attardo; Yineng Wu; Michelle O'Neill; Grace Murilla; Serap Aksoy (Public Library of Science (PLoS), 2017)
Tsetse flies (Glossina spp.) transmit parasitic African trypanosomes (Trypanosoma spp.), including Trypanosoma congolense, which causes animal African trypanosomiasis (AAT). AAT detrimentally affects agricultural activities in sub-Saharan Africa and has negative impacts on the livelihood and nutrient availability for the affected communities. After tsetse ingests an infectious blood meal, T. congolense sequentially colonizes the fly's gut and proboscis (PB) organs before being transmitted to new mammalian hosts during subsequent feedings. Despite the importance of PB in blood feeding and disease transmission, little is known about its molecular composition, function and response to trypanosome infection. To bridge this gap, we used RNA-seq analysis to determine its molecular characteristics and responses to trypanosome infection. By comparing the PB transcriptome to whole head and midgut transcriptomes, we identified 668 PB-enriched transcripts that encoded proteins associated with muscle tissue, organ development, chemosensation and chitin-cuticle structure development. Moreover, transcripts encoding putative mechanoreceptors that monitor blood flow during tsetse feeding and interact with trypanosomes were also expressed in the PB. Microscopic analysis of the PB revealed cellular structures associated with muscles and cells. Infection with T. congolense resulted in increased and decreased expression of 38 and 88 transcripts, respectively. Twelve of these differentially expressed transcripts were PB-enriched. Among the transcripts induced upon infection were those encoding putative proteins associated with cell division function(s), suggesting enhanced tissue renewal, while those suppressed were associated with metabolic processes, extracellular matrix and ATP-binding as well as immunity. These results suggest that PB is a muscular organ with chemosensory and mechanosensory capabilities. The mechanoreceptors may be point of PB-trypanosomes interactions. T. congolense infection resulted in reduced metabolic and immune capacity of the PB. The molecular knowledge on the composition and putative functions of PB forms the foundation to identify new targets to disrupt tsetse's ability to feed and parasite transmission.